Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fneur.2019.00348
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Penumbras of White Matter Hyperintensities and Their Associations With Cognitive Function in Patients With Subcortical Vascular Mild Cognitive Impairment

Abstract: Normal-appearing white matter (NAWM) surrounding white matter hyperintensities (WMHs), frequently known as the WMH penumbra, is associated with subtle white matter injury and has a high risk for future conversion to WMHs. The goal of this study was to define WMH penumbras and to further explore whether the diffusion and perfusion parameters of these penumbras could better reflect cognitive function alterations than WMHs in subjects with subcortical vascular mild cognitive impairment (svMCI). Seventy-three svMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…Seven of the 27 newly identified cross-sectional studies investigated patients with cognitive impairment or dementia; including Alzheimer’s disease (AD), 18, 19 mild cognitive impairment (MCI) 8, 10, 20 and vascular cognitive impairment (VCI). 9, 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of the 27 newly identified cross-sectional studies investigated patients with cognitive impairment or dementia; including Alzheimer’s disease (AD), 18, 19 mild cognitive impairment (MCI) 8, 10, 20 and vascular cognitive impairment (VCI). 9, 21…”
Section: Resultsmentioning
confidence: 99%
“…Since 2016, several studies have been published that provide data on regional or tissue-specific CBF in WMH and normal appearing white matter (NAWM) cross-sectionally, [6][7][8][9][10] as well as longitudinal studies. Therefore, we updated our previous systematic review and meta-analysis 3 to identify whether these gaps in the literature and previous inconsistencies have been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…This matter of fact most likely depends on the severity of the SVD (2, 9-11) and the exact disease stage (9,10,12,(40)(41)(42). WMH may present with impaired blood brain barrier, loss of oligodendrocytes and reduced density of glia, vacuolation and axonal damage and impaired white matter integrity as reported on diffusion tensor imaging (2,9,10,12,(43)(44)(45). However, as in MSL, conventional MRI does not allow for a differentiation of histologically different WMH (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…FA and MD maps of each subject were first coregistered to the corresponding individual T1 3D-SPGR image using the b0 image and then smoothed with a 6 mm full width at half-maximum Gaussian kernel, then resliced into a 2 × 2 × 2 mm 3 voxel-size matrix. According to the previous studies and our recent work (Promjunyakul et al, 2015 , 2016 ; Wu et al, 2019 ), the size of FA and MD penumbras of PVWMH and DWMH were as follows: 6 mm for both FA and MD penumbras of PVWMH, 4 mm for the FA penumbra of DWMH, and 2 mm for the MD penumbra of DWMH. The FA and MD penumbras was gained by summing the FA or MD penumbra of PVWMH and DWMH.…”
Section: Methodsmentioning
confidence: 70%
“…Furthermore, changes in NAWM were found to be associated with a decline in cognitive function as determined by diffusion tensor imaging (DTI; Huang et al, 2007 ; Papma et al, 2014 ; Hirsiger et al, 2017 ). NAWM surrounding WMHs that can only be detected on a microstructural level is referred to as the WMH-penumbra (WMH-P; Maillard et al, 2011 ); neuroimaging studies have revealed damage below the detection threshold in these non-lesioned WM areas (Promjunyakul et al, 2015 , 2016 ; Wu et al, 2019 ). WMH does not fully explain the neuroimaging correlates of cognitive decline in SVCI, as histopathologic alterations in the WMH-P can also lead to CI (Simpson et al, 2007 ; Gouw et al, 2011 ; Promjunyakul et al, 2015 ); however, as these changes are subtle, it may be possible to prevent their aggravation through early intervention.…”
Section: Introductionmentioning
confidence: 99%